Effects of Hypoxia on the Distribution of Calanoid Copepod Eggs in the Seabed Sediments of the Eutrophic Masan Bay, Korea - Seo Yeol Choi (MDPI AG, 2021)
In this study, we investigate the distribution of calanoid copepod eggs in the sediments of Masan Bay (South Sea, Korea), in which hypoxic conditions occur every summer. In August (2011), hypoxia was observed at all stations, while normoxia was observed in April (2012). The pH and hydrogen sulphide concentration at the sediment-water interface in the inner bay during August were 7.7 and >20 mol L−1, respectively, and there was no significant difference between the stations in April. The abundance of eggs in the sediment ranged from 0.69 to 1.49 × 106 eggs m−2 in August, and from 0.59 to 1.08 × 106 eggs m−2 in April. Notably, the proportion of abnormal eggs was high (a maximum of 77.1%) in August, and a uniform distribution of normal eggs (>80%) was observed in April. A generation of abnormal eggs hatched with deformed nauplii in Masan Bay during the summer, and a failure to hatch was likely due to the high H2S concentration and low pH caused by hypoxia. In this paper, we discuss the effects of hypoxia and seabed environments on the hatching success of calanoid copepod eggs.